ß-Methylphenylethylamines: Common fragmentation pathways with amphetamines in electrospray ionization collision-induced dissociation - Brown, David; Hansson, R.; Oosthuizen, F.; Sumner, N. (John Wiley and Sons Ltd, 2015)
β-Methylphenylethylamines are positional isomers of amphetamines and have been discovered in sporting supplements. Although the fragmentation of the β-methylphenylethylamine and N-methyl-β-methylphenylethylamine in gas chromatography-electron ionization-mass spectrometry (GC-EI-MS) systems is significantly different to their amphetamine and methylamphetamine isomers, under electrospray ionization commonly used in liquid chromatography-mass spectrometry (LC-MS) systems, the fragmentation of each of the isomeric pairs is almost identical. The similarities in fragmentation make it possible for the misidentification of the β-methylphenylethylamines as the illicit amphetamines. It is proposed that the similarities are due to a fragmentation pathway involving a common phenonium ion intermediate. By careful control of fragmentation energies in liquid chromatography-tandem mass spectrometry (LC-MS/MS) systems and/or close examination of the relative abundances of product ions formed by collision-induced dissociation (qualifier ratios), it is possible to distinguish the β-methylphenylethylamines from the amphetamines, even if significant retention time separation is not achieved. In liquid chromatography-electrospray ionization-quadrupole time of flight (LC-ESI-QTOF) systems the mass spectra of the β-methylphenylethylamines are identical to their amphetamine isomers. In such systems, retention time separation of the isomers is critical to avoid misidentification. During this study β-methylphenylethylamine and N-methyl-β-methylphenylethylamine have been identified in commercially available sporting supplements and oral fluid samples taken during the course of road-side drugs-in-drivers and workplace testing programmes.